Microbial decontamination of black peppercorns by simultaneous treatment with cold plasma and ultraviolet C. (July 2020) - Bang, In Hee; Kim, Ye Eun; Lee, Seung Young; Min, Sea C.
Abstract: An intervention technology employing simultaneous ultraviolet (UV)-C and cold plasma (CP) treatments was developed to inactivate indigenous mesophilic aerobic bacteria in black peppercorns. At higher UV intensity of UV-CP treatment and water activity of black peppercorns, microbial inactivation levels increased up to 0.6 and 1.7 log CFU/g, respectively. Using a response surface analysis, optimum CP voltage and treatment time for inactivating indigenous bacteria in black peppercorns by UV-CP treatment were predicted to be 10.3 kV and 22.1 min, respectively; these inactivated indigenous bacteria and Bacillus tequilensis spores by 3.4 log CFU/g and 1.7 log spores/g, respectively, with minimal increase in temperature (4.5 ± 1.2 °C). The bacterial inactivation rate (3.4 log CFU/g) achieved by UV-CP treatment was higher than the sum (2.7 log CFU/g) of the inactivation rates of individual UV and CP treatments. UV-CP treatment did not alter the color of black peppercorns and shows potential for application in non-thermal microbial decontamination of black peppercorns. Industrial relevance: This study has developed a novel system for non-thermal microbial inactivation in black peppercorns using simultaneous UV-C and CP treatment (UV-CP treatment). UV-CP treatment was effective in inactivating indigenous bacteria in black peppercorns, including Bacillus tequilensis spores, and had an additive effect on microbial inactivation. The efficacy of treatment in microbial inactivation increased with higher water activity of black peppercorns. The bacterial inactivation efficacy was also influenced by the UV intensity and treatment time. The results of this study demonstrated that UV-CP treatment has the potential to be employed as a non-thermal technology to disinfect black peppercorns and possibly other spices, without affecting their color. Graphical abstract: Unlabelled Image Highlights: UV-CP inactivated indigenous bacteria in black peppercorns by 3.4 log CFU/g. The inactivation level increased by 1.7 log CFU/g as aw increased from 0.1 to 0.7. Optimal UV-CP treatment voltage and time were predicted as 10.3 kV and 22.1 min. UV, CP, and UV-CP treatments yielded 1.5, 1.2, and 3.4 log CFU/g reduction levels. UV-CP treatment effect on indigenous bacteria inactivation was additive.